WIND STRUCTURE OF THE WOLF-RAYET STAR EZ CMA=HD 50896 - Aaron Flores (Revista Mexicana de Astronomía y Astrofísica, 2011)
The Wolf-Rayet star HD 50896 (EZ CMa=WR6) is well-known for the emission-line profile variability that occurs on a 3.7-day timescale. In particular, the shape of the N V 4604-21 doublet changes from a P Cygni profile to one in which no blue-shifted absorption component is present. In this paper we use spectroscopic observations obtained in 1991, 1999, 2005 and 2009 to glean physical conditions within the stellar wind that may give rise to these changes. We find that variations in the opacity at a distance r/Rmax 0.30.5 of the stellar surface can produce the observed effects. Here, Rmax is the extent of the N V line-forming region. The results are consistent either with a scenario in which the opacity of the inner wind region of HD 50896 undergoes cyclical variations over the 3.76 d period or with a quadrupolar wind distribution in which the sectors having different opacities rotate in and out of our line-of-sight on this periodic timescale.